Pengaruh Sulfat Terhadap Kuat Tekan Beton Dengan Variasi Bubuk Kaca Substitusi Semen Dengan W/C 0,4 Dan 0,5 - Fahmi Hidayat; Gunawan Tanzil (Jurnal Teknik Sipil dan Lingkungan, 2013)
The aggressive environment can damage concrete especially sulfate attack which would decrease compressive strength of concrete and also cause corrosion. Therefore, the additive was added into concrete mixture. A glass powder is an additive that contains binding substance in reaction with water and accelerate concrete hardening.This final project will discuss the effect of glass powder as replacement of cement in concrete mixture to concrete compressive strength that soaked in water and water containing sulfate. In this research, concrete sample is cylindrical with diameter of 15 cm and heigth of 30 cm which consisting of normal concrete, 5%, 10%, 15% and 20% glass powder in concrete mixture with w/c 0,4 and 0,5. Soaking is done in two ways, ie soaked in water and water containing sulfate. The concrete compressive strength test was performed at 7,21 and 28 days. The result of this research, the concrete that soaked in water and water containing sulfate has the highest compressive strength on 5% glass powder with w/c 0.4 of 44,92 MPa and 43,78 MPa on 28 days and 5% glass powder with w/c 0,5 of 35,86 MPa and 34,54 MPa on 28 days. Besides of that, the attack of sulfate can decrease compressive strength of concrete which have been soaked in water containing sulfate. The smallest reduction of compressive strength occured on 20% glass powder with w/c 0,4 of 1,70% on 28 days and 20% glass powder with w/c 0,5 of 2,99% on 28 days. It can be concluded, despite the large increase glass powder in concrete mixture can decrease concrete compressive strength, but the effect of sulfate to concrete compressive strength is getting smaller. Â  Keywords: glass powder, sulfate, compressive strength